Identification of Mammal Skins Present in an Ngoni Garment from Malawi Using Mitochondrial DNA Analysis. Issue 2 (3rd April 2022) - Peranteau, Anne; Shepherd, Lara
ABSTRACT: The study of material culture is increasingly including techniques based on DNA sequencing. This article describes the use of mitochondrial DNA (mtDNA) sequencing to identify mammal skins in a Malawian garment (chibbiya). The object had been described in historic museum records as being made with "tails of the sacred black and white monkey". However, it contains a number of different colored and patterned pelts, suggesting that it was constructed from a variety of animals. Three different sampling techniques, including a recently developed noninvasive sampling method, were used to obtain DNA from twelve locations on the object. Human DNA contamination presented a challenge to species identification, but this was overcome using a method to block human DNA. The sequence data obtained were matched against the online reference database GenBank and indicated that seven mammal species were used to construct the garment but only two of these were primates. For the baboon sequence, published studies enabled the likely geographic region of origin to be established. Our mtDNA analysis overcame limitations of hair fiber analysis, namely the lack of known reference samples for comparison, and resulted in an enhanced understanding of methods and practices used in Ngoni culture.